(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Irawati W, Pinontoan R, Yuwono T. 2020. Indigenous copper resistant bacteria isolated from activated sludge of water treatment plant in Surabaya, Indonesia. Biodiversitas 21: 5077-5084. Biological wastewater treatment using activated sludge is a promising wastewater treatment solution for removing heavy metals. To improve the effectiveness of biological wastewater treatment, activated sludge must consist of bacteria that can remove heavy metals through the process of bioaccumulation and biosorption. This study was aimed to isolate indigenous copper resistant bacteria and determining their resistance to copper, as well as analyzing their ability to accumulate and remove copper. Copper resistant bacteria were isolated from activated sludge of water treatment plant in industrial plant in Rungkut, Surabaya. Resistance to copper was analyzed by determining the value of minimum inhibitory concentration (MIC). The ability of bacterial isolates to remove copper was analyzed by atomic absorption spectrophotometer. A total of six highly copper resistant bacteria were isolated and designated as B6.1, C8.1, C9.3, C9.4, C9.5, C10.4 isolates. All isolates were categorized as high resistant bacteria with the MICs of 9-11 mM CuSO4. The two highest copper resistant bacteria were isolates C10.4 and C9.4. The ability of the two isolates to accumulate copper was 8.02 mg and 4.83 mg per gram dry weight of cells and to remove of copper up to 20.45% and 17.66%, respectively.